Literature Review : The Effect of Service Quality on Patient Satisfaction During the Covid-19 Pandemic Based on SRVQUAL Scale - Ascobat Gani; Dian Agnesa Sembiring; Riki Yedija Lumban Tobing (Sarana Ilmu Indonesia (salnesia), 2022)
The Covid-19 pandemic has forced hospital management need to take quick action in overcoming the crisis while maintaining and improving the relationships with the customers in order to remain satisfied with the quality of service in hospitals. The study’s goal was to use SRVQUAL Scale to describe the impact of service quality on patient satisfaction during the Covid-19 (reliability, tangibles, empathy, assurance, responsiveness). This paper was a literature review sourced from Pubmed and ProQuest articles with keywords (